Embracing the Other: The Transformative Spirit of Love - Vadana , Roby (Journal of Dharma, 2016)
Grace Ji-Sun Kim, Embracing the Other: The Transformative Spirit of Love, Cambridge: Wm. B. Eerdmans Publishing Company, 2015, pages:182, ISBN: 978-0-8028-7299-9.